Review of Under Age Marriage Law Pregnant Out of Marriage and the Impact - Angling Angling; Evita Isretno Israhadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper describes the impact of early marriage. By using normative legal research methods, with literature as a data search, as well as descriptive analysis to present the data comprehensively. The results of the study indicate that the legal impact is contrary to the marriage law, so it requires a judicial process in obtaining the permit.